Cabaran dan Solusi dalam Kerja-kerja Membaik Pulih Bangunan Komersial Terbengkalai: Perspektif Kontraktor - Awang Merah, Siti Nur Fatihah; Masrom, Md. Asrul Nasid (Research in Management of Technology and Business, 2023)
Johor Bahru is one of the rapidly developing cities in Malaysia, however it is polluted with numbers of abandoned commercial buildings. This problem continues for a long period of time, and it has contributed to a negative impact on the country’s economic growth. Effective ways to improve the situation are still under research. Therefore, this study aims to explore the major problems faced by new contractors when carrying out the process of improving abandoned projects as well as studying improvement measures for repairing abandoned commercial buildings. Qualitative methods and interviews were used to collect and analyze information data from respondents. To achieve the objectives of this study, the researcher interviewed 3 contractors to obtain appropriate information related to abandoned commercial buildings. The researcher used a pilot study test to verify the data collection. The results of this study showed that the rehabilitation process of this abandoned building has caused problems for new contractors. The findings of this study indicate improvement measures in the repair work of this abandoned building. Finally, to prevent the construction industry in Malaysia from continuing to be plagued by the problem of abandonment, contractors need to identify a good and systematic management system in terms of finance, work progress on site and so on to prevent projects from being abandoned.